Recent advances in the roles of cultural and personal values in organizational behavior - Nedelko, Zlatko, 1983-; Brzozowski, Maciej, 1975- (IGI Global, 2020)
"This book examines how culture and personal values shape and influence organizational members' actions and behavior, leadership styles, decision making processes, innovativeness, perceptions of corporate social responsibility, and formulation of strategies and goals in organizations"--Provided by publisher.